2016
DOI: 10.5688/ajpe806107
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Health Information Technology and Pharmacy Informatics in a Pharmacy Professional Didactic Curriculum -with a Team-based Learning Approach

Abstract: Objective. To incorporate a pharmacy informatics program in the didactic curriculum of a team-based learning institution and to assess students' knowledge of and confidence with health informatics during the course. Design. A previously developed online pharmacy informatics course was adapted and implemented into a team-based learning (TBL) 3-credit-hour drug information course for doctor of pharmacy (PharmD) students in their second didactic year. During a period of five weeks (15 contact hours), students use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…There was some evidence that e-learning interventions could result in an intention to change practice (outcome level 3 of Kirkpatrick's model) and these studies deserve some further examination as possible predictors for success of e-learning. As would be expected, these studies involved mostly qualified pharmacists [11,12,14,16] with only one study involving pharmacy interns [59] and two studies involving pharmacy undergraduates [23,37]. These seven studies [11,12,14,16,23,37,59] involved several different delivery methods of the e-learning intervention and thus, no relationship could be established between delivery method and success.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There was some evidence that e-learning interventions could result in an intention to change practice (outcome level 3 of Kirkpatrick's model) and these studies deserve some further examination as possible predictors for success of e-learning. As would be expected, these studies involved mostly qualified pharmacists [11,12,14,16] with only one study involving pharmacy interns [59] and two studies involving pharmacy undergraduates [23,37]. These seven studies [11,12,14,16,23,37,59] involved several different delivery methods of the e-learning intervention and thus, no relationship could be established between delivery method and success.…”
Section: Discussionmentioning
confidence: 99%
“…Learning was also assessed subjectively, through pre-, mid-and post-intervention surveys in twenty-six (46.4%) studies [11,12,[14][15][16][17][18][19]23,25,29,30,35,37,[41][42][43]45,46,50,52,56,57,59,62,64] and all but two [19,42] of these studies reported that the e-learning intervention was effective. Taglieri et al, [19] investigated the effect of completion of online virtual patient cases on student performance and confidence in mock clinic visits.…”
Section: Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Health informatics courses have also been developed at several schools of pharmacy. 16,[23][24][25] As noted in the section on connecting care and modernizing skills, all clinicians should achieve foundational literacy in health informatics and clinical data management to use with individual patients and populations. To fully achieve the potential of learning health systems however, a significantly larger cadre of health IT experts is needed.…”
Section: Accelerating Real-world Evidence and Advancing Sciencementioning
confidence: 99%